2016
DOI: 10.7554/elife.17936
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of mTOR Complex 1 and 2 for T follicular helper cell differentiation and germinal center responses

Abstract: T follicular helper (Tfh) cells play critical roles for germinal center responses and effective humoral immunity. We report here that mTOR in CD4 T cells is essential for Tfh differentiation. In Mtorf/f-Cd4Cre mice, both constitutive and inducible Tfh differentiation is severely impaired, leading to defective germinal center B cell formation and antibody production. Moreover, both mTORC1 and mTORC2 contribute to Tfh and GC B cell development but may do so via distinct mechanisms. mTORC1 mainly promotes CD4 T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 79 publications
(100 reference statements)
3
104
1
Order By: Relevance
“…Rescue of the rapamycin phenotype when only transferred B cells carried the Mtor F2108L mutation confirmed that mTORC1 was required in a B cell-specific manner, rather than acting through other relevant cell types that rely on this pathway for differentiation and function, such as Tfh cells (Ray et al, 2015; Yang et al, 2016; Zeng et al, 2016). We expect that this chemical-genetics approach, and the Mtor F2108L mice in particular, will be useful to others to address the roles of mTORC1 in other settings, without the kinetic limitations of conditional mouse genetics.…”
Section: Discussionmentioning
confidence: 89%
“…Rescue of the rapamycin phenotype when only transferred B cells carried the Mtor F2108L mutation confirmed that mTORC1 was required in a B cell-specific manner, rather than acting through other relevant cell types that rely on this pathway for differentiation and function, such as Tfh cells (Ray et al, 2015; Yang et al, 2016; Zeng et al, 2016). We expect that this chemical-genetics approach, and the Mtor F2108L mice in particular, will be useful to others to address the roles of mTORC1 in other settings, without the kinetic limitations of conditional mouse genetics.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, recent studies using conditional knockout mice showed that mTORC1 signaling was essential for induction of Tfh responses (30,31). These contradictory results may be explained by the different approaches used to silence mTOR activity.…”
Section: Discussionmentioning
confidence: 89%
“…9 In humans, IL-12, IL-6, and TGFβ have been implicated in Tfh cell development. 49,50 This distinct mode of metabolic reprogramming may stem from the need for fully differentiated Tfh cells to survive in the GC, where glucose may become limiting due to the extensive proliferation undergone by GC B cells. 27,28 Unlike mouse Tfh cells, in which development is inhibited by TGFβ, 29 human TGFβ is found to synergize with IL-12 and IL-23, which also signals through STAT4, to enhance STAT3-STAT4 signaling and promote Tfh cell differentiation.…”
Section: At B Eg Inning : Tfh Cell S De Velop In the Outer T Cell Zmentioning
confidence: 99%